Electrical contact effects of flexible self-supporting DNA thin films for storage devices. (2nd February 2023) - Kokkiligadda, Samanth; Kesama, Mallikarjuna Reddy; Jeon, Sohee; Jeong, Jun-Ho; Park, Sung Ha
Abstract: The development of flexible DNA thin films embedded with diverse functional nanomaterials might be beneficial for electronic devices and biosensors. In this work, we fabricated two different types of electrodes (i.e. metal paste spotted electrodes and metal layer electrodes) on flexible drug- and dye-embedded DNA thin films to examine their electrical and capacitance properties for conduction and energy storage, respectively. Enhanced current and reduced capacitance of drug-embedded DNA thin films compared with pristine DNA with Ag paste electrodes were observed due to the intrinsic characteristics of the drugs. We used the electron-beam deposition process to fabricate relatively large-area metal-coated (e.g. Au and Al) electrodes, which ensures the creation of metal layers on both sides of the flexible thin films while improving metal contact. There was a significant current increase in DNA thin films with metal layer electrodes compared with DNA thin films with Ag paste electrodes. Furthermore, capacitances measured from Au/DNA/Au and Al/DNA/Al capacitors were relatively more stable than from Ag paste DNA thin films. The physical properties of our samples might be easily controlled by manipulating functional nanomaterials in DNA thin films and various types of metal layer electrodes. Our self-supporting DNA thin films with integrated nanomaterials and durable metal layer electrodes might be employed in flexible electronic devices such as nanogenerators, skin electronics and biosensors in the future.